Molecular and Functional Characterization of Odorant Binding Protein 7 From the Oriental Fruit Moth Grapholita molesta (Busck) (Lepidoptera: Tortricidae) - Chen, Xiu-Lin; Li, Guang-Wei; Xu, Xiang-Li; Wu, Jun-Xiang (Frontiers in Physiology, 2018)
Odorant-binding proteins (OBPs) are widely and abundantly distributed in insect sensillar lymph and are essential for insect olfactory processes. The OBPs can capture and transfer the odor molecules across the sensillum lymph to odorant receptors and trigger the signal transduction pathway occur. In this study, a putative OBP gene, GmolOBP7, was cloned using specific-primers based on the unigene annotated form the antennal transcriptome of Grapholita molesta. Real-time PCR (qRT-PCR) analysis revealed that GmolOBP7 was highly expressed in wings of males and antennae of both sex adult moths, and low levels in other tissues. The recombinant GmolOBP7 (rGmolOBP7) was successfully expressed and purified via Ni-ion affinity chromatography. The results of binding assays showed that rGmolOBP7 exhibited a high binding affinity to minor sex pheromone 1-dodecanol with Ki of 7.48 µM, and also had high binding capacities to host-plant volatiles, such as pear ester, lauraldehyde and α-ocimene. RNA-interference experiments were performed to further assess the function of GmolOBP7. qRT-PCR showed that the levels of mRNA transcripts significantly declined in 1- and 2-d-old male and female moths treated with GmolOBP7 dsRNA compared with those non-injection controls. EAG responses of dsRNA-injected males and females to pear ester and males to 1-dodecanol were significantly reduced compared to GFP-dsRNA-injected and non-injected controls. We infer that the GmolOBP7 have dual functions in perception and recognition of host-plant volatiles and sex pheromones.